Organoleptic Characteristics of Cookies from Sorghum Composites Flour - E., Wulandari; E., Sukarminah; I., Lanti; F., Sufmawati (KnE Life Sciences, 2017)
Application of wheat flour in various food products has increased the import of wheat flour over years. The use of domestically grown crops like Sorghum (Sorghum bicolor L. Moench) could reduce the demand of wheat. Sorghum flour can be used in partial substitution with wheat flour for many food products, like cookies. The use of sorghum as cookies ingredient could be combined with other flours to get a composite flour. The purpose of this research was to obtain proportion of sorghum flour, sweet potato flour and soyabean flour that produce cookies with good organoleptic characteristics. The proportion of composite flour adequacy was calculated using a list of foodstuffs (DKBM).The research method was based on Experimental Method with Randomized Block Design (RBD) in twelve treatments and two repetitions. The treatments were proportion of sorghum flour (6 minutes, 8 minutes, 10 minutes of dehulling time), sweet potato flour, and soyabean flour. The results showed that cookies made with proportion of sorghum flour, sweet potato flour, and soyabean flour gave no significant difference in organoleptic characteristics (Overall, color, taste, aroma, and hardness). The result also showed that the characteristics of the cookies were not affected by dehulling of sorghum grains but influenced by other ingredient than flour. Keywords: Sorghum, Sweet Potato Flour, Soyabean Flour, Cookies, Sensory Properties